Local edge antimagic coloring for chain of path and cycle - Walfried, Yosua; Chandra, Ivana Joice; Silaban, Denny Riama (Indonesian Combinatorial Society (InaCombS), 2025)
Let G=(V,E) be a simple connected graph with vertex set V and edge set E. A local edge antimagic labeling of G is a bijection f:V (G)→1, 2, 3, ... , |V(G)| where the weights of any two adjacent edges of G are distinct. The weight of an edge uv is defined as w(uv) = f(u)+f(v). By assigning the color w(uv) to each edge uv ∈ E(G), we obtain a proper local edge antimagic coloring of G. The minimum number of colors required for edge coloring induced by the local edge antimagic labeling is called a local antimagic chromatic index of G. In this article, we give the exact value of the local antimagic chromatic index for the chain of path and cycle graphs.